Role of airline promotion activities in destination branding: Case of Dubai vis-à-vis Emirates Airline - Rashad Al Saed; Amitabh Upadhya; Mohammad Abu Saleh (European Research on Management and Business Economics (ERMBE), 2020)
Dubai, the globally known Emirate of the United Arab Emirates, has achieved an image of its own as a sun, sand and sea destination with the added X-factor of safety and shopping to enhance visitors' positive perceptions. Equally well perceived by consumers and envied by competitors, its national carrier, Emirates Airline, has made a substantial contribution to Dubai's branding as a tourist destination. This study investigates Emirates Airlines' promotional activities and their impact on Dubai's brand image. The study then creates a conceptual model of destination attributes, brand image and airline promotional activities, which provide the basis for empirical analysis. The results, conforming to the conceptual model, show that the national carrier's promotional activities and in-flight services have a significant and positive impact on Dubai's branding image. The study finds an interesting correlation between the promotional efforts of a national carrier and branding of destinations and provides recommendations for enhanced co-branding.
Keywords: M31; Z33; 650; Airline promotion; Co-branding; Destination branding; Dubai